2021
DOI: 10.1007/s12350-021-02575-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of TTR cardiac amyloidosis among patients undergoing bone scintigraphy

Abstract: Amyloidosis is an important cause of infiltrative cardiomyopathy and is often diagnosed lately in the course of the disease; radiolabeled bisphosphonates bone scan is highly sensitive in detecting transthyretin (TTR) cardiac amyloidosis; data on the true prevalence of cardiac involvement in TTR amyloidosis are lacking. The aim of the present retrospective observational, monocentric study was to estimate the prevalence of positive bone scan suspect for TTR cardiac amyloidosis in the population of Piedmont -a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 13 publications
7
32
1
1
Order By: Relevance
“…Specific clinical settings have been recognized as strongly associated with CA but further studies are needed to better characterize these populations, mainly to stratify patient risk and evaluate which patients are ideal candidates for the newly available disease-modifying therapies. Acknowledgments: We would like to thank all the nuclear medicine doctors, hematologists, neurologists, pathologists and nephrologists of the participating centres for providing their essential [8,[13][14][15][16]20,27,28,33,[36][37][38][39]41,42,[46][47][48][49][50][51][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific clinical settings have been recognized as strongly associated with CA but further studies are needed to better characterize these populations, mainly to stratify patient risk and evaluate which patients are ideal candidates for the newly available disease-modifying therapies. Acknowledgments: We would like to thank all the nuclear medicine doctors, hematologists, neurologists, pathologists and nephrologists of the participating centres for providing their essential [8,[13][14][15][16]20,27,28,33,[36][37][38][39]41,42,[46][47][48][49][50][51][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1. Prevalence of CA in different screening studies[8,[13][14][15][16]20,27,28,33,[36][37][38][39]41,42,[46][47][48][49][50][51][54][55][56].…”
mentioning
confidence: 99%
“…Notably, of those with suspected ATTR-CA (grade 2/3), 41% had a history of HF prior to scan ( 80 ). Bianco et al found a prevalence of 0.54% grade 2/3 uptake on 3,228 scans performed over 5 years using DPD or HDMP at their center ( 86 ). With higher clinical suspicion, ATTR-CA may have been suspected in some of these patients as 48% had prior HF, 34.8% had known neuropathy, and 21.7% had carpal tunnel syndrome.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…With higher clinical suspicion, ATTR-CA may have been suspected in some of these patients as 48% had prior HF, 34.8% had known neuropathy, and 21.7% had carpal tunnel syndrome. However, 21.7% were entirely asymptomatic highlighting the existence of an asymptomatic disease state during which treatment could prevent disease progression ( 86 ).…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…For example, approximately one in eight patients undergoing transcatheter aortic valvular replacement [12] and about one in five patients with left ventricular hypertrophy and heart failure (HF) could be diagnosed with ATTR-CA [13]. ATTR-CA is nowadays an important clinical reality for both cardiologists [11] and radiologists [14]. In ATTR-CA, deposition of transthyretin (TTR) amyloid fibrils occurs in the extracellular space of the heart, affecting not only the ventricles but the atria, as well as resulting in impaired ventricular and atrial function [15][16][17].…”
Section: Introductionmentioning
confidence: 99%